Portfolio assessment in AI-enhanced learning environments: a pathway to emotion regulation, mindfulness, and language learning attitudes - Mohamad Ahmad Saleem Khasawneh; Alaa Aladini; Sabah Abdulkader Assi; Bemnet Ajanil (Language Testing in Asia)
Abstract In recent years, the incorporation of artificial intelligence (AI) into instructional settings has sparked important interest in how it can develop different aspects of language learning, principally in the realm of assessment. While traditional assessment methods have long been central to evaluating learners’ progress, the rise of AI tools presents an opportunity to revolutionize assessment practices by providing more personalized and adaptive feedback. This study explored the significance of portfolio assessment in AI-assisted environments, focusing on its impact on academic emotion regulation (AER), mindfulness, and attitudes toward language learning. A total of 69 students (38 in the experimental group (EG) and 31 in the control group (CG) from Bahir Dar University, Bahir Dar, Ethiopia, aged 22–34 years, participated in this quasi-experimental study. The participants, enrolled in the final term of their Bachelor’s program in English Teaching, were randomly assigned to either the EG or CG. The EG engaged in a portfolio assessment approach where AI was employed by the course instructor to review the portfolios and provide continuous, individualized feedback. Conversely, the CG also followed a portfolio assessment approach but relied on traditional teacher-led feedback without AI integration. The study employed pretests and posttests to measure AER and mindfulness levels before and after the intervention. Additionally, an attitude questionnaire was administered to the EG to assess their perceptions of AI-based portfolio assessment. Data analysis included analysis of covariance (ANCOVA), independent sample t-test, and one-sample t-test to determine the effects of the intervention. The findings indicated the potential of AI-assisted portfolio assessment in enhancing AER and mindfulness while fostering positive attitudes toward language learning. By comparing AI-integrated and traditional approaches, this study provides valuable insights into the role of AI in promoting effective and engaging learning experiences in EFL contexts.